Evaluation of Texas Home Instruction for Parents of Preschool Youngsters Program on Reading and Math Achievement for Grades K to 8 - Abdulaziz, Noor Amal Saud (University of North Texas, 2019)
This study was intended to evaluate the impact of socioeconomically disadvantaged children's participation in the Texas Home Instruction for Parents of Preschool Youngsters (TX HIPPY) Program on their school readiness and academic achievement. The study used a quasi-experimental design and applied full and optimal propensity score matching (PSM) to address the evaluation concern of the impact of the TX HIPPY program on HIPPY participants' academic achievement compared to non-HIPPY participants. This evaluation targeted former HIPPY participants and tracked them in the Dallas ISD database through Grade Levels K-8. Data were obtained by administering Istation's Indicators of Progress (ISIP) for kindergarten, TerraNova/SUPERA for Grades K-2, and State of Texas Assessments of Academic Readiness for math and reading (STAAR) for Grades 3-8. HIPPY and non-HIPPY groups were matched using propensity score analysis procedures. The evaluation findings show that the TX HIPPY program positively influences kindergarten students to start school ready to learn. The findings of math and reading achievements suggest that HIPPY children scored at the same level or higher than non-HIPPY children did on math and reading achievement, indicating that TX HIPPY program has achieved its goal of helping children maintain long-term academic success. However, the evaluation findings also indicated that the impact evaluation framework must be designed with attention to higher-level factors beyond academic achievement that influence children's academic success.